Eqüidade e reforma em sistemas de serviços de saúde: o caso do SUS Equity and reform in health services system: the case of Unified Health System of Brazil - Jairnilson Silva Paim (Universidade de São Paulo, 2006)
O ensaio procurou responder a seguinte pergunta: o SUS é uma política pública de promoção da eqüidade? Nesse sentido, apresenta alguns delineamentos prévios sobre certas noções presentes na pergunta, especialmente sobre as concepções de eqüidade e do SUS. Realiza uma breve revisão sobre reformas setoriais em contraponto com a Reforma Sanitária Brasileira e um sumário do perfil de desigualdades em saúde no país. Conclui examinando alguns esforços para a redução dessas desigualdades levantando a hipótese de que o SUS pode promover eqüidade no sentido de justiça sem comprometer o seu caráter universal e igualitário. This paper aimed to answer the following question: Is SUS a public policy of equity promotion? In this direction, it presents previous thoughts on some terms, especially on the concepts of equity and on SUS. A brief review is carried out on sector's reforms in order to discuss the Brazilian Sanitary Reform. Also, a summary of health inequalities profile in the country is given. It concludes by examining some efforts for the reduction of these inequalities by formulating the hypothesis that SUS can promote equity in the direction of justice without compromising its universal and egalitarian character.